Local enhancement of the material properties of aluminium sheets by a combination of additive manufacturing and friction stir processing. Issue 1 (2019) - Mondal, Mounarik; Das, Hrishikesh; Hong, Sung-Tae; Jeong, Byeong-Seok; Han, Heung Nam
Abstract: Friction stir processing (FSP) is combined with additive manufacturing (AM) with selective laser melting to locally enhance the material properties of a metallic part. A groove inside aluminium 1060 alloy sheet is filled with an aluminium 7075 alloy powder by AM. FSP is then applied to the AMed region along the groove. The suggested technique creates a heterogeneous microstructure with alternating reinforcement-enriched and matrix-enriched regions. While the overall hardness of the stir zone (SZ) increases significantly, the heterogeneous microstructure results in a unique uneven hardness distribution in the SZ. Tensile tests confirm the effectiveness of the suggested technique.